Maize–legume intercropping promote N uptake through changing the root spatial distribution, legume nodulation capacity, and soil N availability - Ben-chuan ZHENG; Ying ZHOU; Ping CHEN; Xiao-na ZHANG; Qing DU; Huan YANG; Xiao-chun WANG; Feng YANG; Te XIAO; Long LI; Wen-yu YANG; Tai-wen YONG (Journal of Integrative Agriculture, 2022)
Legume cultivars affect N uptake, component crop growth, and soil physical and chemical characteristics in maize–legume intercropping systems. However, how belowground interactions mediate root growth, N fixation, and nodulation of different legumes to affect N uptake is still unclear. Hence, a two-year experiment was conducted with five planting patterns, i.e., maize–soybean strip intercropping (IMS), maize–peanut strip intercropping (IMP), and corresponding monocultures (monoculture maize (MM), monoculture soybean (MS), and monoculture peanut (MP)), and two N application rates, i.e., no N fertilizer (N–) and conventional N fertilizer (N+), to examine relationships between N uptake and root distribution of crops, legume nodulation and soil N availability. Results showed that the averaged N uptake per unit area of intercrops was significantly lower than the corresponding monocultures. Compared with the monoculture system, the N uptake of the intercropping systems increased by 31.7–45.4% in IMS and by 7.4–12.2% in IMP, respectively. The N uptake per plant of intercropped maize and soybean significantly increased by 61.6 and 31.8%, and that of intercropped peanuts significantly decreased by 46.6% compared with the corresponding monocultures. Maize and soybean showed asymmetrical distribution of roots in strip intercropping systems. The root length density (RLD) and root surface area density (RSAD) of intercropped maize and soybean were significantly greater than that of the corresponding monocultures. The roots of intercropped peanuts were confined, which resulted in decreased RLD and RSAD compared with the monoculture. The nodule number and nodule fresh weight of soybean were significantly greater in IMS than in MS, and those of peanut were significantly lower in IMP than in MP. The soil protease, urease, and nitrate reductase activities of maize and soybean were significantly greater in IMS and IMP than in the corresponding monoculture, while the enzyme activities of peanut were significantly lower in IMP than in MP. The soil available N of maize and soybean was significantly greater increased in IMS and IMP than in the corresponding monocultures, while that of IMP was significantly lower than in MP. In summary, the IMS system was more beneficial to N uptake than the IMP system. The intercropping of maize and legumes can promote the N uptake of maize, thus reducing the need for N application and improving agricultural sustainability.